The Welsh lord's convenient bride - Morgan, Lissa (Harlequin historicals., 2022)
Hiding a disfigurement, Eleanor de Vraille is already lacking confidence when she arrives at her future husband's cheerless Welsh castle. And Rhun ab Owain's open disapproval of her does nothing to make her feel at ease. Their union is to seal peace between their families, nothing more. But Eleanor's heart rebels--is she a fool to hope for any affection from this strong-willed nobleman with the dark glittering eyes?